Psychological Status of a Sample of Elderly People Living with their Families and Residing in Dar Al-Wafa for the Elderly and the Aged in the City of Tripoli - Alwaseea, Najia; Fawzia Ahmed, (AlQalam Journal of Medical and Applied Sciences, 2025)
This study was conducted to examine the psychological state of a sample of elderly people residing with their families and residing in the Al-Wafa Home for the disabled and the elderly in the city of Tripoli, to know the extent of the elderly's need to use medical technologies for psychosocial support and health care. The comparative descriptive approach was used in the study. The research sample consisted of 80 elderly men and women aged 60 years and over, 40 respondents residing with their families, including 20 males, 20 females, and 40 respondents residing in Al-Wafa House for the disabled and the elderly (22 males, 18 females). To achieve the objectives of the study, a psychological state scale was used, which was filled out through a personal interview. The results of the study revealed that there were statistically significant differences between the two research samples of the elderly in the care home and those residing with their families in general. The level of their psychological state for a sample of elderly people residing in Al-Wafa House for the disabled and the elderly. أجريت هذه الدراسة بهدف دراسة الحالة النفسية لدى عينة من المسنين المقيمين مع أسرهم والمقيمين في دار الوفاء للعجزة والمسنين بمدينة طرابلس. استخدم في الدراسة المنهج الوصفي المقارن ،وقد تكونت العينة البحثية من (80) مسنا ومسنة ممن يبلغ أعمارهم 60 سنة فأكثر ، (40) مبحوث من المقيمين مع أسرهم منهم (20 من الذكور، 20 من الإناث) و(40) مبحوث من المقيمين في دار الوفاء للعجزة والمسنين (22 من الذكور ،18 من الإناث)، ولتحقيق أهداف الدراسة تم استخدام مقياس الحالة النفسية حيث ملئ بالمقابلة الشخصية، وقد توصلت نتائج الدراسة عن وجود فروق ذات دلالة إحصائية بين عينتي البحث من المسنين في دار الرعاية والمقيمين مع اسرهم. في مجمل مستوى الحالة النفسية لهم لصالح عينة المسنين المقيمين في دار الوفاء للعجزة والمسنين